Anmeldelser - Redaktionen, - (Geografisk Tidsskrift, 1969)
Litteraturanmeldelser: FYSISK GEOGRAFI M. M. Geotektonische Forschungen, Heft 29 og 30 (K. H.) ......................... 83 Geotektonische Forschungen, Heft 31 (K. H.) ................................ 98 Geophysik und Geologie, Folge 12 (K. H.) ................................... 84 Maack: Kontinentaldrift und Geologie des südatlantischen Ozeans (K. H.) . . 84 Knopoff, Drake & Hart: The Grust and Upper Mantle of the Pacific Area IK. H.) .................................................................... 84 Degens: Geochemie der Sedimente (K. H.) ................................... 85 West: Pleistocene Geology and Biology (K. H.) ............................ 85 Woldstedt: Quartär IK. H.) ................................................... 98 Hallesches Jahrbuch für mitteldeutsche Erdgeschichte (K. H.) ............. 98 Thornbury: Principles of Geomorphology (K. H.) ......................... 100 Strahler: Physical Geography (R. H. J.) ..................................... 87 Resske: Topographie, Morphologie und Morphogenese einer Eisrandlage (B. F.) .................................................................... 88 Ollier: Weathering (N. K. J.) ................................................. 100 Thurner: Hydrogeologie (S. R.) .............................................. 86 Kneese & Smith: Water Research (S. R.) ..................................... 86 World Weather Records (R. H. J.) ............................................ 87 Sulakvelidze et al.: Formation of Precipitation and Modification of Hail Processes (K. M. J.)........................................................ 99 Wood: Microbiology of Oceans and Estuaries (N. K. J.) .................... 101 Rodin & Bazilevich: Production and Mineral Cycling in Terrestrial Vegetation (S. C.) .............................................................. 87 KARTOGRAFI M. M. Bratt: En krönika om svenska glober (N. N.) ................................ 81 KULTUR- OG ERHVERVSGEOGRAFI Bogue: Principles of Demography (H. M.) .................................. 93 Matthiessen: Befolkningsproblemer (R. H. J.) ............................... 94 Witthauer: Verteilung und Dynamik der Erdbevölkerung (R. H. J.) ........ 95 Keyfitz & Flieger: World Population (R. H. J.) .............................. 95 Bognar: Economic Policy and Planning in Developing Countries (S. F.) . . 96 Stycos: Human Fertility in Latin America (Aa. Aa.) ....................... 96 Peach: West Indian Migration to Britain (Aa. Aa.) ......................... 97 Lewis: History and Social Anthropology (C. G. F.) ......................... 99 Dasmann: Environmental Conservation (N. K. J.) .......................... 102 Otremba: Der Wirtschaftsraum (R. H. J.) ................................... 102 Masefield et al.: The Oxford Book of Food Plants (R. II. J.) ............. 103 Blankenburg & Cremer: Handbuch der Landwirtschaft und Ernährung in den Entwicklungsländern (S. C.) ....................................... 98 Lugmair: Die Landmaschinenerzeugung in Österreich (M. .1.) ............. 90 Michelic: The Political Element in the Port Geography of Trieste (Aa. Aa.) 90 EUROPA OG SOVJETUNIONEN Leser: Landeskundlicher Führer durch Rheinhessen (R. H. J.) ............. 91 Habbe: Die würmzeitliche Vergletscherung des Gardasee-Gebietes (B. F.) . . 98 Pounds: Eastern Europe (Aa. Aa.) .......................................... 92 Ökonomische Geographie der Deutschen Demokratischen Republik (Aa. Aa.) 101 FREMMEDE VERDENSDELE Weitz & Rokach: Agricultural Development (Israel) (R. H. .1.) ............. 92 Spate & Learmonth: India and Pakistan (S. F.) .............................. 93 Hansen: Med Margethe og Henrik i Nepal (A. S.) ........................... 93 Raunkiaer: Through Wahhabiland on Camelback (N. N.) .................. 82 Meyers Kontinente und Meere: Afrika (C. G. F.) ........................... 92 Ratzel: Aus Mexico (N. N.) ................................................... 82 Christensen & Harper: The Mississippi-Ohio Confluence Area (R. H. J.) . . 94 Jack-Hinton: The Search for the Islands of Solomon (S. C.) ................ 83 POLAREGNENE Amer. Geogr. Soc.: Primary Productivity of the Antarctic and Subantarctic (B. F.) .................................................................. 89 Hofmann: Geobotanische Untersuchungen in Spitzbergen (B. F.) ........ 89 Gad: Grønlands Historie II (B. F.) ............................................ 89 Amer. Geogr. Soc.: Distribution of Marine Invertebrates S. of 35° S Latitude (B. F.) ............................................................... 99 ATLASVÆRKER OG KORT Humboldt: Mexico-Atlas (N.N.) .............................................. 80 Dept, of Nat. Development: Atlas of Australian Resources (S. C.) ........ 83 Thorén: Picture Atlas of the Arctic (B. F.) ................................... 89